NF-κB as a Target for Modulating Inflammatory Responses - Gasparini, Chiara; Feldmann, Marc (Current Pharmaceutical Design, 2012)
The inflammatory response is of major importance in host defence, but is involved in all acute and chronic diseases. Multiple inflammatory cells and molecules are involved. Among the latter, the Nuclear Factor -κB (NF-κB) has been found to be most important and present in all cell types. NF-B regulates the expression of a large number of genes involved in inflammation. NF-κB plays a key role in the orchestration of the multifaceted inflammatory response, not only in the first pro-inflammatory phase, but also later in the regulation of the resolution of inflammation, when anti-inflammatory genes are expressed and apoptosis is induced. The review describes NF-κB and its two pathways: the canonical, mediated by the p65 and p50 subunits, and the non-canonical, mediated by the subunits RelB, p52 and p50. The relevance of the kinases and interactions leading to NF-κB activation is considered in different primary cells (i.e. macrophages, dendritic cells, fibroblasts, cells from inflammatory tissues), together with the response induced and the ligand involved. Then we overview the different steps to NF-B activation that can be targeted (IKKs, IκBα or NF-κB subunits themselves) with various technologies available i.e. small molecules peptides or nucleic acids. A rationale is provided for possible targets to consider, in the light that NF-κB signaling pathways regulates both pro-inflammatory and anti-inflammatory responses. The possibility of using NF-κB targeted dendritic cells in immunotherapy is considered.
Keywords: NF-κB